Rhizosphere ecology of lumichrome and riboflavin, two bacterial signal molecules eliciting developmental changes in plants - Dakora, Felix D.; Matiru, Viviene; Kanu, Alfred S. (Frontiers in Plant Science, 2015)
Lumichrome and riboflavin are novel molecules from rhizobial exudates that stimulate plant growth. Developmental changes elicited by lumichrome at very low nanomolar concentrations (5 nM) include early initiation of trifoliate leaves, expansion of unifoliate and trifoliate leaves, increased stem elongation and leaf area, and consequently greater biomass accumulation in monocots and dicots. However, higher lumichrome concentration (50 nM) depressed root development and reduced growth of unifoliate and second trifoliate leaves. Applying either 10 nM lumichrome, 10 nM ABA, or 10 ml of infective rhizobial cells (0.2 OD600) to roots of monocots and dicots for 44 h produced identical effects, which included decreased stomatal conductance and leaf transpiration in Bambara groundnut, soybean and maize, increased stomatal conductance and transpiration in cowpea and lupin, and elevated root respiration in maize (19% by rhizobia and 20% by lumichrome). Extracellular exudation of lumichrome, riboflavin and IAA was greater in N2-fixing rhizobia than non-fixing bacteria, indicating their role as symbiotic signals. Xylem concentration of lumichrome in cowpea and soybean was greater in plants inoculated with infective rhizobia and treated with lumichrome (61.2 µmol lumichrome.ml-1 sap), followed by uninoculated plants receiving lumichrome (41.12 µmol lumichrome.ml-1 sap), and lowest in uninoculated, lumichrome-free plants (26.8 µmol lumichrome.ml-1 sap). Overall, soybean showed greater xylem concentration of lumichrome and a correspondingly increased accumulation in leaves relative to cowpea. As a result, soybean exhibited dramatic developmental changes than cowpea. Taken together, lumichrome and riboflavin secreted by soil rhizobia function as environmental cues for sensing stress. The fact that exogenous application of ABA to plant roots caused the same effect as lumichrome on stomatal functioning suggests molecular cross-talk in plant response to environmental stimuli.